Multi-Objective Optimization of The Buffer Allocation Problem Considering The Overall Equipment Effectiveness Indicator - Hernández-Vázquez, José Israel; Hernández-Vázquez, José Omar; Hernández-González, Salvador; Martínez-González, Adrián (International Journal of Industrial Engineering: Theory, Applications and Practice, 2025)
This paper presents a formulation of the buffer allocation problem of a parallel serial production line of a footwear stitching process. This was analyzed under a multi-objective optimization approach that aims to maximize the value of the Overall Equipment Effectiveness indicator used in Lean Manufacturing, as well as to minimize the total cost of buffer allocation, this being a new proposal in the buffer allocation problem solution. The case study involves unreliable operating conditions. Process times, times between failures, and repair times are considered Normal distribution functions. The evaluation method used in the study involves the use of a simulation meta-model built from a design of experiments and simulations of the production line; also, the Evolutionary Solver algorithm is used to provide a solution to the mathematical model. The results report the allocation of buffers and their impact on the objectives, as well as a comparison between the optimization criteria.